2021
DOI: 10.1021/acsami.0c17886
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Control of the Li0.9Mn1.6Ni0.4O4 Spinel Structure with Enhanced Electrochemical Performance

Abstract: The development of more sustainable societies has become an urgent goal worldwide. Electrical batteries are currently seen as one of the most important energy storage technologies for the development of decarbonized societies. However, many lithium-ion battery manufacturers currently utilize cobalt, a toxic and hazardous mineral, in their batteries. Lithium-deficient manganese nickel oxide spinels are considered promising candidates owing to their high potential and environmental friendliness. Their electroche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…For lithium vacancies, while V − Li (removing a Li + ion) generates little disturbance to the system, V 0 Li (removing a Li atom) reveals the delithiation mechanism. 16,86 A localised hole is observed on the Ni in proximity to the defect site, with a magnetisation of −0.9 m B which is nearly half of the original value (−1.7 m B ) for Ni 2+ . This suggests that Ni 2+ (d 8 ) is oxidised to Ni 3+ (d 7 ) low-spin conguration, with the Bader charge of 1.33 compared to 1.21 for bulk Ni 2+ in agreement with the reduction in Ni-O bond lengths from 2.05 Å to 1.86-2.05 Å.…”
Section: Phase Stabilitymentioning
confidence: 89%
See 2 more Smart Citations
“…For lithium vacancies, while V − Li (removing a Li + ion) generates little disturbance to the system, V 0 Li (removing a Li atom) reveals the delithiation mechanism. 16,86 A localised hole is observed on the Ni in proximity to the defect site, with a magnetisation of −0.9 m B which is nearly half of the original value (−1.7 m B ) for Ni 2+ . This suggests that Ni 2+ (d 8 ) is oxidised to Ni 3+ (d 7 ) low-spin conguration, with the Bader charge of 1.33 compared to 1.21 for bulk Ni 2+ in agreement with the reduction in Ni-O bond lengths from 2.05 Å to 1.86-2.05 Å.…”
Section: Phase Stabilitymentioning
confidence: 89%
“…4 The disordered phase generally exhibits better cycling stability and rate capability than the ordered phase, however the connection between disorder and performance has remained unclear, with increasing attention placed on understanding the role of cation disorder. [14][15][16][17][18][19][20][21][22] While some studies found that Mn/Ni disorder increases with oxygen vacancy and Mn 3+ formation, others have suggested that the "disordered" phase from different studies is likely to be samples with partial cation disordering, a varying degree of oxygen content and impurity phases. 13,19,20,[23][24][25] Regardless, the correlation between cation disorder and oxygen content has made it difficult to distinguish the key driving factor for improved performance, illustrating the need to decouple these effects and study their impacts independently.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation